Static Bioassay and Toxicity of Azo Dye Stuff to the Air Breathing Fish Heteropneustes fossilis and Its Possible Rectification - Joshi, Smita; Nemawarkar, Sonal; Birla, Shailaja (Asian Journal of Chemistry, 2010)
This paper deals with the calculation of the toxicity of synthesized azo dye stuffs and its complexes with 3d transition metal ions on H. fossilis up to 30 days at a durational interval of 5, 10, 20 and 30 days. Sublethal, LD50 and LD doses were found out by taking different concentrations of azo dye and its complexes with 3d transition metals like Fe2+ and Co2+. The extent of lethality was measured by behavioural changes all over the body on exposure to azo dye and its complex.